2008
DOI: 10.1111/j.1748-1716.2008.01853.x
|View full text |Cite
|
Sign up to set email alerts
|

5‐HT1A, but not 5‐HT2 and 5‐HT7, receptors in the nucleus raphe magnus modulate hypoxia‐induced hyperpnoea

Abstract: These data suggest that 5-HT acting on 5-HT(1A) receptors in the NRM increases the hypoxic ventilatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…We also observed that LC noradrenergic neurons play no role in basal ventilation [7]. Additionally, previous studies from our laboratory demonstrated that microinjections of WAY-100635 and Ketanserin in the preoptic area [22] and nucleus raphe magnus [42] did not affect ventilation during normocapnia. Recently, we observed that a reduction of approximately 80% of LC noradrenergic neurons was associated with a large decrease (∼64%) in the ventilatory response to CO 2 , indicating that LC exerts an important excitatory influence on CO 2 drive to breathing [7].…”
Section: Discussionsupporting
confidence: 50%
“…We also observed that LC noradrenergic neurons play no role in basal ventilation [7]. Additionally, previous studies from our laboratory demonstrated that microinjections of WAY-100635 and Ketanserin in the preoptic area [22] and nucleus raphe magnus [42] did not affect ventilation during normocapnia. Recently, we observed that a reduction of approximately 80% of LC noradrenergic neurons was associated with a large decrease (∼64%) in the ventilatory response to CO 2 , indicating that LC exerts an important excitatory influence on CO 2 drive to breathing [7].…”
Section: Discussionsupporting
confidence: 50%
“…The 5-HT 1A autoreceptors in dorsal raphé nuclei and other brain regions are involved in regulating the firing of serotonergic neurons (Zifa and Fillion, 1992). Activation of 5-HT 1A R increases phrenic nerve activity (Wilken et al, 1997; Teng et al, 2003; Wang et al 2007; Nucci et al, 2008; Valic et al, 2008) and induces an increase in phasic and tonic genioglossus muscle activity important for tongue protrusion and the prevention of airway obstruction (Besnard et al, 2007). 5-HT 1A R also exerts excitatory modulation on respiratory rhythm generation (Hilaire et al, 1997), and, when co-activated with 5-HT 2A R, it is reportedly involved in the depolarization of PBC neurons (Schwarzacher et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies demonstrate an important recruitment of 5-HT pathways in response to hypoxia. 5-HT acting on 5-HT1A receptors in the nucleus raphe magnus plays no role under normal conditions but modulates breathing during hypoxia (38). In the anteroventral preoptic region, both 5-HT1A and 5-HT7 receptors are involved in the inhibitory modulation of the hypoxic ventilatory response (39).…”
Section: Discussionmentioning
confidence: 99%